1996
DOI: 10.1597/1545-1569(1996)033<0277:broaba>2.3.co;2
|View full text |Cite
|
Sign up to set email alerts
|

Biologic Responses of Autogenous Bone and Beta-tricalcium Phosphate Ceramics Transplanted into Bone Defects to Orthodontic Forces

Abstract: This study was conducted to evaluate biologic responses of autogenous bone (particulate marrow and cancellous bone; PMCB) and beta-tricalcium phosphate ceramics (TCPC) to orthodontic stimuli. Nine dogs served as the experimental animals; three dogs underwent orthodontic tooth movement after grafting, three dogs received PMCB grafting without tooth movement, and three dogs received TCPC grafting without tooth movement. Immediately after extraction of the upper second and/or third incisors, the maxillary alveola… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0
1

Year Published

2009
2009
2020
2020

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(11 citation statements)
references
References 0 publications
1
9
0
1
Order By: Relevance
“…There was only mesial tipping of incisors as a result of gingival fibres stretching in response to the forces applied during the expansion. Autogenous bone grafting to fill the bony defect provided a continuous alveolar crest, offering support for mesial root movement by orthodontic treatment. The functional recovery after bone grafting by teeth movement prevents additional bone resorption.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…There was only mesial tipping of incisors as a result of gingival fibres stretching in response to the forces applied during the expansion. Autogenous bone grafting to fill the bony defect provided a continuous alveolar crest, offering support for mesial root movement by orthodontic treatment. The functional recovery after bone grafting by teeth movement prevents additional bone resorption.…”
Section: Discussionmentioning
confidence: 99%
“…There was no evidence of root resorption in the central incisors, contrary to that described in previous reports. Root resorption was reported as a consequence of orthodontic tooth movement, which was not performed during bone graft healing.…”
Section: Discussionmentioning
confidence: 99%
“…Este tipo de procedimientos está indicado en casos en los que vaya a pasar un gran lapso de tiempo entre el momento de realizar la extracción y el momento del cierre del espacio, disminuyendo con estos procedimientos el riesgo de colapso del reborde [4,[42][43][44][45][46].…”
Section: Motivo De La Remisiónunclassified
“…β-TCP is biocompatible (Rosa et al 1995, Hossain et al 1996, Ohsawa, et al 2000 , ,and achieves favorable volumetric maintenance. (Breitbart et al 1995, ;Gao et al 1997) In a comparative histomorphometric study in miniature pigs (Merten et al 2001), β-TCP has shown very favorable qualities of biodegradation and substitution.…”
Section: Biomaterials For Guided Bone Regeneration In the Jaws -Animamentioning
confidence: 99%